136k views
1 vote
Which standard form equation below correctly represents the quadratic function

y = -1/3(x-3)² + 2
1) y = -1/3x² - 2x -1
2) y = -1/3x² + 2x + 5
3) Now of the choices are correct
4) y = -1/3x² + 2x - 1

1 Answer

5 votes

Answer: 4) y = -1/3x² + 2x - 1

Explanation:

Given :

y =
(-1)/(3)
(x-3)^(2) + 2

Expanding (x-3)² will give :


x^(2) - 6x + 9

substituting into the function , we have :

y =
(-1)/(3)
( [tex]x^(2) - 6x + 9 ) + 2

Expanding , we have

y =
(-1)/(3)
x^(2) + 2x - 3 + 2

y =
(-1)/(3)
x^(2) + 2x - 1

User Najette
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.